Pendampingan Penyusunan Laporan Penjualan Konsinyasi Berbasis Microsoft Excel pada UMKM - Septiani, Dwi; Ferdiansyah; Sunarto (UNIB Press, 2024)
The issue faced by the MSME partners of Warung Jajanan Hafshah is their inability to create consignment sales reports that adhere to accounting standards. To address these challenges, the initiative focuses on providing support to these partners, aiming to enhance their skills in compiling consignment sales reports. The community service program employs mentoring, discussions, and feedback methods with the partners. As a result of this initiative, the MSME partners have successfully developed and implemented consignment sales reports using Microsoft Excel in a systematic manner. Through the mentoring sessions conducted, it is evident that partners are now capable of generating consignment sales reports both manually and systematically. Additionally, a key outcome of this community service activity includes the publication of findings in a national journal.